Executive Committee Minutes 2005-02-17 - Academic Senate:::::::::
Faculty Governance Release Time for '05-'06, Priority Registration Policy, Course Repeat Policy and Procedures, Posthumous Degree request from Modern Languages, Policy for Access to Programs for Students and Others with Disabilities, WASC update